Cross-border protection of personality rights in the European Union - Cedeño Hernán, Marina (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
Cross-border disputes over the rights of individuals raise important legal issues as regards both jurisdiction and applicable law. The exclusion of this matter from the scope of the Rome II Regulation on the law applicable to non-contractual obligations makes the determination of international jurisdiction particularly important.Article 7(2) of the Brussels I-bis Regulation establishes a special rule of jurisdiction in matters of tort, delict, or quasi-delict, in favor of the State in whose territory the damage occurred or is likely to occur. Determining that place is not easy, especially if the medium used for the injury of the right is the Internet. This paper analyses the prolific and controversial case law of the ECJ on the interpretation of Article 7(2) of the Brussels I-bis Regulation and the new rules of international jurisdiction created by the Court.
Keywords: international jurisdiction; rights of the personality; Brussels I-bis Regulation; Rome II Regulation